The Relevant Clues: Information Behaviour and Assessment in Classic Detective Fiction - Gainor, Rhiannon (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The paper presents the first of two research project phases. It examines narrative analysis of fiction as an appropriate research methodology for studying information behaviour, using detective novels published 1920 - 1950. An information behaviour model has been generated, to be tested in Phase II against established models and other research. Cette communication présente la première de deux phases d’un projet de recherche. Il s’agit d’une analyse narrative d’œuvres de fiction comme méthodologie de recherche appropriée pour l’étude des comportements informationnels dans les romans policiers publiés entre 1920 et 1950. Le modèle de comportement informationnel qui s’en dégage sera testé lors de la seconde phase et sera comparé aux modèles et aux travaux de recherche existants.